2016
DOI: 10.1039/c6nr01351a
|View full text |Cite
|
Sign up to set email alerts
|

Dysprosium electrodeposition from a hexaalkylguanidinium-based ionic liquid

Abstract: The rare-earth element dysprosium (Dy) is an important additive that increases the magnetocrystalline anisotropy of neodymium magnets and additionally prevents from demagnetizing at high temperatures. Therefore, it is one of the most important elements for high-tech industries and is mainly used in permanent magnetic applications, for example in electric vehicles, industrial motors and direct-drive wind turbines. In an effort to develop a more efficient electrochemical technique for depositing Dy on Nd-magnets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…The rare‐earth element Dy is used in industries because of its high magnetic moment and the highest saturation magnetization of any element . It also shows excellent durability at high temperatures . These properties may be benefit for us to find efficient and durable NRR catalyst.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The rare‐earth element Dy is used in industries because of its high magnetic moment and the highest saturation magnetization of any element . It also shows excellent durability at high temperatures . These properties may be benefit for us to find efficient and durable NRR catalyst.…”
Section: Figurementioning
confidence: 99%
“…It is expected that the electrons movement in rare‐earth nanocrystals would be limited in two or/and all directions, which may reduce the competition of hydrogen evolution reaction (HER) during the electrolysis. The rare‐earth element Dy is used in industries because of its high magnetic moment and the highest saturation magnetization of any element . It also shows excellent durability at high temperatures .…”
Section: Figurementioning
confidence: 99%
“…The electrodeposition of REEs and elements such as Fe, Ni or Co in the form of films from aqueous solutions has been reported. [8] However, this suggests that the electrodeposition of REEs from non-aqueous solvents might offer a promising alternative, [9] although it is recently reported that 0.4 wt.% of water in the electrolyte facilitate the deposition of Nd. This hydrogen then increases the pH of the solution, thereby favouring the formation of REE hydroxides and oxides.…”
Section: Introductionmentioning
confidence: 99%
“…[12] In particular, metals which are inaccessible from plating in aqueous solutions can efficiently be deposited with non-aqueous electrolytes/ionic liquids. [13,14] In contrast to ionic liquids, the components of a DES can easily be purified before mixing via established methods such as recrystallization or sublimation. In addition, most compounds are easily accessible, hence at low cost and environment-friendly.…”
Section: Introductionmentioning
confidence: 99%